Effects of microstructural anisotropy and helium implantation on tensile properties of powder-metallurgy processed tungsten plates. (March 2022) - Miyazawa, Takeshi; Matsui, Kento; Hasegawa, Akira
Highlights: Effects of microstructural anisotropy and He implantation on the tensile properties of PM-W plates were investigated. Microstructural anisotropy was observed in total elongation at temperatures lower than 500 °C. A decrease in ductility were observed along thickness direction. The effect of He on crack propagation was significant along the thickness direction. Abstract: Powder metallurgy (PM)-processed tungsten (W) materials subjected to rolling are being developed for the monoblock divertors of fusion reactors. PM-W exhibits high dislocation density, fine grains, and a layered grain structure, which is introduced by the rolling process. It is expected that its microstructure control will be improved by the brittleness of PM-W at low temperatures. However, it is well known that, in rolled metals, the grain structure depends on the rolling ratio, direction, and temperature. This can cause anisotropy in the mechanical properties. The purpose of this study was to elucidate the effects of microstructural anisotropy and helium (He) implantation on the tensile properties of PM-W plates. The PM-W plates subjected to rolling and stress relief were examined. Miniature tensile specimens were prepared along the following three directions: the tensile directions were parallel to the rolling direction (L.D.), perpendicular to the rolling direction (T.D.), and parallel to the thickness direction (S.D.). The He implantation experiments were performed using a 50 MeV He 2+ ion beam of a cyclotron accelerator. The implanted He concentration was approximately 20 appm. Tensile tests were conducted at 100–1100 °C and the ruptured surfaces were observed by scanning electron microscopy. From the results of the as-received condition, microstructural anisotropy was observed in the case of total elongation at temperatures lower than 500 °C. Cracks formed owing to intergranular fracture were observed at the edges of the gauge section along S.D., and anisotropy was observed in the tensile fracture behavior. It is assumed that the cracks tend to propagate along the layers of the grain boundaries. Although the ductility remained almost unchanged along the T.D. after He implantation, a decrease in ductility and brittle fracture were observed along the S.D.. Thus, the effect of He on crack propagation was significant along the S.D..